Lesson study in the continuous education of teachers who teach mathematics: a context view of national scenario - Morgana Scheller; Eduardo Rafael Zimdars (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This article presents an overview of Lesson Study (LS) productions in the continuing education of teachers who teach mathematics, to identify and understand what is being developed and researched in Brazilian context. Eleven articles that compose the corpus of analysis indicate that LS is conceived, mainly, as a methodology in the context of courses with teachers from the early years, focusing on learning problems related to Number. They investigate aspects related to the contributions or limitations of the LS and analyze the professional development of the participating teachers, with a tendency to report experiences to suggest studies on the national scene. The results reaffirm and expand previous studies. We conclude that the LS in continuing education is recent and quite punctual in Brazil, but it consents education from the perspective of professional development, in which collaboration between participants is highlighted, thus breaking with models that are still in force.